Arthroscopic Abrasion Arthroplasty Is Not Superior to Ligament Reconstruction and Tendon Interposition for Thumb Carpometacarpal Arthritis. (November 2019) - Rog, Dominik; Ozyurekoglu, Tuna; Karuppiah, Kumar K.
Background: A few arthroscopic options have been proposed for the treatment of early stages of the arthritis of the thumb carpometacarpal (CMC) joint. The purpose of this study was to compare the results of arthroscopic abrasion arthroplasty with ligament reconstruction and tendon interposition (LRTI).Methods: In this retrospective cohort study, 11 patients who underwent thumb CMC joint arthroscopic abrasion arthroplasty were compared with 15 patients who were randomly selected from a group of 80 LRTI arthroplasty patients during the same study period, with a minimum 1 year follow-up. Preoperative and postoperative evaluations included radiographs and measurements of grip strength, visual analog scale (VAS) pain scores, and Disabilities of the Arm, Shoulder and Hand (DASH) scores.Results: The mean preoperative VAS score in both groups was 6.8. Mean preoperative DASH scores were 61.1 in the arthroscopy group and 67.4 in the LRTI group. Postoperative VAS score at final follow-up was 4.8 in the arthroscopy group and 1.2 in the LRTI group ( P < .05). Postoperative DASH scores 9 months after surgery were 23 for the LRTI group and 55.2 for the arthroscopy group ( P < .05). Eight patients in the arthroscopy group had a second surgery due to persistent pain.Conclusions: Patients undergoing arthroscopic abrasion arthroplasty had high revision rates, higher postoperative pain, and lower patient-rated outcomes than patients undergoing LRTI procedure. The poor results in the arthroscopy group may be secondary to the inherent instability of the CMC joint and lack of use of any biological or artificial interposition material.